The role of the Paris Agreement in sustainable development and economic growth of the European Union - Kovalova, Angelina (Riga Graduate School of Law, 2024)
The environmental and climate goals put out by the European Union (EU) are among the most ambitious and comprehensive in the world. Thus, the work describes how climate policy have been developed and established. The central role of the Bachelor Thesis is given to two key legal documents on climate change – the Kyoto Protocol and the Paris Agreement. The Thesis aims to analyse the history of the documents, the EU’s main commitments under it, as well as the impact on sustainable development and economic growth of the European Union. With the help of identifying the commitments EU took under the agreements, the authors comes to the conclusion on the strong impact of the legal documents on sustainable development and positive impact on the economic growth of the EU due to the increase in Gross Domestic Product and investments’ activity by 2030.
Keywords: Research Subject Categories::LAW/JURISPRUDENCE::Other law::European law; Research Subject Categories::LAW/JURISPRUDENCE::Other law::International law; Environmental law; Kyoto Protocol; Paris Agreement; sustainable development